Proximal sensing of Cu in soil and lettuce using portable X-ray fluorescence spectrometry - Sacristán, D.; Viscarra Rossel, Raphael; Recatalá, L. (Elsevier Science, 2016)
This article demonstrates the use of proximal sensing for rapid assessment of Cu concentrations in agricultural soil and lettuce ( Lactuca sativa L.) using portable X-ray fluorescence (P-XRF) spectrometry. We show that the approach is adequate for the screening of Cu contamination in agricultural soil. Biomass assays were conducted with Cu contaminated agricultural soil and lettuce ( Lactuca sativa L.), and we collected samples from soil, roots and stems and leaves. The samples were measured with the P-XRF and the spectra were analysed to identify the Cu energy bands. The full width at half height (FWHH) and the maximum height of the Cu peak in the energy spectra were correlated with Cu concentrations that we determined using conventional analytical methods. Results show that P-XRF is a good technique for assessing soil contaminated with Cu. Results for roots and stems/leaves were not as accurate as those for soil. However, there is potential for this technique to be used as a first-pass measure to assess the Cu concentrations in plants because it is rapid and requires very little sample preparation. There is also scope to improve the approach using multivariate statistics. P-XRF sensing provides a useful alternative for the screening soil and plants that are contaminated with Cu, and potentially also other heavy metals. It is faster, cheaper, non-destructive and practical compared to conventional laboratory methods that rely on wet chemistry.